Incorporating safety features into cycling clothing for night cycler's in Malaysia / Nurul Husna Rashidah Mohd Sofian and Rose Dahlina Rusli - Mohd Sofian, Nurul Husna Rashidah; Rusli, Rose Dahlina (Universiti Teknologi MARA, 2020)
Night-time cycling is particularly problematic, and most jurisdictions legislate the use of reflective clothing, lights, and reflective devices. This research discussed incorporating safety features into cycling clothing for night cyclers in Malaysia. This scenario shows that Lack of safe functional clothing is suitable for the weather and low light when night cycler. It's becoming much more critical for cyclists to stay on top of ensuring their safety as the number of vehicles that travel day and night increases. The objectives of this research are: (i) To identify the suitable design element of incorporating safety features into cycling clothing for cyclists. (ii) to analyse the safest colours to wear at night for cyclists. (iii) to determine the potential of creating cycling clothing design embedded with safety features especially for nighttime. The research will distribute the data from ask-interview, documentation, look- observation, ask- pilot survey, experimentation material, and so all. The focus people to interview or survey cause for in cyclers group, people who have a passion for the safety clothing industry, academicians, and so all. Therefore, this research will be focused on enhancing visibility, protection, and comfortable clothing for cyclists. The result from this research showed that there is a great potential of creating cycling clothing design embedded with safety features especially for nighttime.